Pengetahuan Personal Hygiene Berhubungan Dengan Timbulnya Gejala Penyakit Kulit Pada Petugas Pengangkut Sampah - Putu Firda Ika Nahrajanti; i Wayan Sudiadnyana (Jurnal Kesehatan Lingkungan (JKL), 2020)
Knowledge of personal hygiene is very important to note by the garbage collector to maintain their life , health and welfare in prevent symptoms of skin diseases. This research to find out the knowledge of the personal hygiene with the symptoms of a skin disease in the garbage collector. This type research is analytic survey on the interview with the cross sectional.The sample as many as 70 officers garbage, located in the Badung Regency. Data were collected by using a questionnaire and statistical analysis by using the Chi Square test. The result from the garbage collector knowledge are about 12,9% have a good knowledge, about 32,8% have an averange knowledge and about 54,3% have a bad knowledge. Respondents with some symptoms as much as 58,6 % and some who were not as symptoms is as much as 41.1 % . Symptoms of skin disease most often happen by the garbage collector were itchy, red stain, redness of the skin , bumps, scaly skin, and peeling skin. Chi Square statistical results P value  = 0,000 ɑ (0.05), which means there is a significant relationship between the level of knowledge about personal hygiene with the onset of symptoms of skin diseases in the garbage collector with a moderate level of relationship (CC value = 0.537). The garbage collector should further enhance his knowledge of personal hygiene by given counseling.